Defective nickel zirconium oxide mesoporous bifunctional electrocatalyst for oxygen evolution reaction and overall water splitting. (1st February 2023) - Sadaqat, Maira; Manzoor, Sumaira; Aman, Salma; Nisar, Laraib; Najam-Ul-Haq, Muhammad; Shah, Afzal; Shawky, Ahmed M.; Elhosiny Ali, H.; Ashiq, Muhammad Naeem; Taha, T.A.
Graphical abstract: Highlights: A single phase zirconium nickel oxide has been synthesized by simple sol-gel method. Zr0.012 Ni4.3 O0.68 has activity only 294 mV overpotential at 10 mA cm −2 . The conductivity and oxygen vacancies increase as a function of Ni concentrations. The synthesized material is also efficient toward overall water splitting. Abstract: Designing a robust electrocatalyst for Oxygen evolution reaction (OER) and other energy transformation devices is still challenging. To meet this trial, numerous oxides and bimetallic oxides consisting of oxygen vacancies spring up a critical parameter for outstanding OER electrocatalyst. In this work, for the first time, single-phase zirconium nickel oxide (ZrNi4 O) nanospheres with different concentrations of Ni are fabricated by a facile sol-gel method. Among all the synthesized series of ZrNi4 O, Zr0.012 Ni4.3 O0.68 deposited on glassy carbon (GC) electrode exhibits remarkable OER performance requiring only 294 mV overpotential at 10 mA cm −2 . Such unusual performance is owing to the availability of a huge number of various oxygen vacancies created in the non-stoichiometric compound Zr0.012 Ni4.3 O0.68 . In addition to this, the effect of substrate and medium on Zr0.012 Ni4.3 O0.68 is also investigated. The Zr0.012 Ni4.3 O0.68 is also analyzed as overall electrocatalyst for electrolysis in two electrode system requiring only 1.55 V cell voltage for 20mAcm −2 current density. As the concentration of Ni varies in Zrx Ni4-x Oσ, the amount of oxygen vacancies increases in cubic system of ZrNi4 O, consequently enhancing the conductivity of the electrode. That ultimately augments the intrinsic activity (specific activity) and empirical usage (Mass activity) of electrocatalysts toward OER.